Inkjet Printing of High Aspect Ratio Superparamagnetic SU-8 Microstructures with Preferential Magnetic Directions - Loïc Jacot-Descombes; Maurizio R. Gullo; Victor J. Cadarso; Massimo Mastrangeli; Olgaç Ergeneman; Christian Peters; Philipe Fatio; Mouhamad A. Freidy; Christofer Hierold; Bradley J. Nelson; Jürgen Brugger (Micromachines, 2014)
Structuring SU-8 based superparamagnetic polymer composite (SPMPC) containing Fe3O4 nanoparticles by photolithography is limited in thickness due to light absorption by the nanoparticles. Hence, obtaining thicker structures requires alternative processing techniques. This paper presents a method based on inkjet printing and thermal curing for the fabrication of much thicker hemispherical microstructures of SPMPC. The microstructures are fabricated by inkjet printing the nanoparticle-doped SU-8 onto flat substrates functionalized to reduce the surface energy and thus the wetting. The thickness and the aspect ratio of the printed structures are further increased by printing the composite onto substrates with confinement pedestals. Fully crosslinked microstructures with a thickness up to 88.8 μm and edge angle of 112° ± 4° are obtained. Manipulation of the microstructures by an external field is enabled by creating lines of densely aggregated nanoparticles inside the composite. To this end, the printed microstructures are placed within an external magnetic field directly before crosslinking inducing the aggregation of dense Fe3O4 nanoparticle lines with in-plane and out-of-plane directions.